The effects of mobile payment on consumer behavior. Issue 3 (5th October 2020) - Liu, Yuewen; Luo, Junlong; Zhang, Long
Abstract: With the advancement of technology and diversification of payment methods, mobile payment methods have gradually replaced traditional cash payments and become the mainstream payment mode. Although mobile payment is more convenient, is it faster than cash payment when their physical differences are controlled? Does it affect consumer behavior? We designed two studies to explore these questions. In Study 1, we required 192 participants to physically pay by cash or mobile phone and measured their willingness to pay (WTP). In Study 2, we compared the speed of the two payment methods when the physical differences between them were eliminated and measured consumers' willingness to buy from 46 students. Our results indicated that the effect of mobile payment, which increases WTP, also applies to specific products, and it does not occur if the money is a gift, as opposed to if it is earned. Moreover, when the process of cash payment is made as easy as mobile payment, people still spend less time on mobile payments than cash payment, and mobile payment effect is impacted by payment time. The above results supplement the evidence that payment methods have an impact on consumer behavior, and provide consumers, merchants, and regional managers with suggestions on payment methods.